2019
DOI: 10.4103/aian.aian_349_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition in Parkinson's disease and correlation with gastrointestinal symptoms

Abstract: Background:Parkinson's disease (PD) patients are at a higher risk of malnutrition with the overall prevalence estimated to be 3%–60%, but there are limited data in India regarding nutritional assessment of PD.Aim:This study aims to assess nutritional status of PD patients and correlate the disease factors and gastrointestinal tract (GIT) symptoms with nutritional status.Materials and Methods:The PD cohort was assessed for demographic factors, nutritional assessment was done by Mini-Nutritional Assessment (MNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…MNA is a questionnaire used for whole-body health evaluation, including body weight change, appetite, and body figure. In our study, we found that patients at risk of malnutrition according to their MNA scores were also at risk of constipation, and this finding was similar to what was reported for those with Parkinson' s disease [30].…”
Section: Discussionsupporting
confidence: 89%
“…MNA is a questionnaire used for whole-body health evaluation, including body weight change, appetite, and body figure. In our study, we found that patients at risk of malnutrition according to their MNA scores were also at risk of constipation, and this finding was similar to what was reported for those with Parkinson' s disease [30].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have observed that PD patients generally suffer from gastrointestinal disorders and GM dysbiosis prior to displaying motor symptoms [40][41][42][43]. In addition, we have found in the patients examined dysphagia and swallowing disturbances.…”
Section: Gastrointestinal Pathology In Parkinson Diseasesmentioning
confidence: 49%
“…Although more likely to be present in patients with advanced PD, dysphagia may develop early in the course of PD [61]. Dysphagia increases the risk of malnourishment and malnutrition in patients with PD [62], and dysphagia severity predicts a poor outcome in persons with advanced PD [63]. Dysphagia for pills is an often overlooked aspect of dysphagia in PD and may be evident in close to 30% of patients, particularly those with more advanced disease [64].…”
Section: Dysphagiamentioning
confidence: 99%